-١ - أثر برنامج الكورت في تنمیة التفكیر الإبداعي لدى طلبة معاھد إعداد المعلمین - م .د أحـــــــمد داوود سلـمان; م .د أحمد عبد الستار عبد الواحد (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملـخص : یرمي البحث الحالي تعرف أثر برنامج الكورت في تنمیة التفكیر الإبѧداعي لѧدى طلبѧѧة معاھѧѧد إعѧѧداد المعلمѧѧین، ولتحقیѧѧق أھѧѧداف البحѧѧث وضѧѧع الباحثѧѧان فرضѧѧیتین صفریتین وكالاتي : - ١ -لایوجѧѧد فѧѧرق ذو دلالѧѧة إحصѧѧائیة بѧѧین المتوسѧѧطین الحسѧѧابیین لѧѧدرجات افѧѧراد المجموعة التجریبیة والمجموعھ الضѧابطة فѧي اختبѧار التفكیѧر الإبѧداعي البعѧدي لѧدى طلبة الصف الثاني في معاھد إعداد المعلمین . ٢ -لایوجѧѧد فѧѧرق ذو دلالѧѧة إحصѧѧائیة بѧѧین المتوسѧѧطیین الحسѧѧابیین لѧѧدرجات الѧѧذكور ودرجات الإناث في المجموعة التجریبیة فѧي اختبѧار التفكیѧر الإبѧداعي البعѧدي لѧد ى طلبѧة الصѧف الثѧاني معاھѧد إعѧداد المعلمѧین. ولغѧرض إكمѧال متطلبѧات البحѧث اطلѧع الباحثѧان علѧى ادبیѧات ونظریѧات تخѧص محѧاور الموضѧوع كمѧا اطلعѧوا علѧى بعѧض الدراسѧѧات السѧѧابقة التѧѧي تناولѧѧت محѧѧاور موضѧѧوع البحѧѧث ، اتبѧѧع الباحثѧѧان المѧѧنھج التجریبي في اجراءات بحثھما لملائمتھ لأھѧداف البحѧث ،تألفѧت عینѧة البحѧث مѧن ٦٠ طالب وطالبة بواقع ٣٠ طالѧب وطالبѧة لكѧل مѧن المجمѧوعتین التجریبیѧة والضѧابطة ، كافأ الباحثان بین المجموعتین في اختبار قدرات التفكیѧر الابѧداعي القبلѧي ، التحصѧیل الدراسي للاب والام ، اعتمد الباحثان أختبار التفكیر الابداعي الذي اعده الكبیسي عام ١٩٨٨) والمعتمد أصلا ً علѧى اختبѧار جلفѧورد) الѧذي تكѧون مѧن خمѧس فقѧرات لقیѧاس عناصѧر التفكیѧر الابѧداعي ، توصѧل الباحثѧان الѧى نتѧائج تѧم ذكرھѧا فѧي فصѧل عѧرض النتائج ومناقشتھا كما اورد الباحثان بعض الاستنتاجات والتوصیات والمقترحѧات فѧي نھایة بحثھما . Abstract : The Effect of Cort in Developping the Innovative Thinking for Students of Teacher Training Institute Lect. Asst. Ahmed Dawood Salman Lec. Dr. Ahmed AbdulSattar Abdul-Wahid Diyala University Teacher Training Institute Rusafa First Ministry of Education العدد الخامس والخمسون . مجلة الفتح . ایلول لسنة ٢٠١٣ م.د. احــمد داود سلـــمان م.د. احمد عبد الستار عبد الواحد -٢ - The present study aims knowing the Effect of Program in Developing the Innovative Thinking for Students of Teacher Training Institute. In order to achieve the objectives of the study the researcher put the following zero hypotheses: 1. there is no statistically significant differences between the arithmetic means and the scores of the experimental group and the control groups in innovative thinking for the students of the second grade in innovative thinking. 2. There is statistically significant differences between arithmetic means for the male and the female in the in innovative thinking for the students of the second grade in innovative thinking. In order to complete the requirements of the study, the researchers reviewed the literature and theories and the theories. The researcher followed the experimental approach in the procedures to make them suiting with the suitability for the study. The sample was made up of 60 students as 30 male female for each group. The researcher matched the two groups in the test of innovative thinking, parent education, and they adopted the innovative test adopted by Al-Kubaisy 198 (adopted by Clifford ) which is made up of five items to measure the in innovative thinking. The researcher comes up to the results which were mentioned and discussed. They also mentioned some conclusions and recommendations and suggestions at the end of their study